2001
DOI: 10.1046/j.1439-0310.2001.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Differences between Feral Pigeons and Zenaida Doves: The Role of Neophobia and Human Proximity

Abstract: Learning differences predicted from ecological variables can be confounded with differences in wariness of novel stimuli (neophobia). Previous work on feral pigeons (Columba livia), as well as on group‐feeding and territorial zenaida doves (Zenaida aurita), reported individual and social learning differences predicted from social foraging mode. In the present study, we show that speed of learning a foraging task covaries with neophobia and latency to feed from a familiar dish in the three types of columbids. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 21 publications
5
47
0
Order By: Relevance
“…This discrepancy may reflect methodological differences. In contrast to our experiments, the test subjects in the studies by Seferta et al (2001) and Webster & Lefebvre (2001) were never habituated to the foraging task apparatus to the extent that they fed from it within their normal, or 'control', latency to feed. Indeed, the research literature supports Greenberg's (2003) remark that animals shying away from unfamiliar situations, as reflected by, for example, their object neophobia, are unlikely to assess the costs and benefits of a novel foraging opportunity such as finding the solution to a novel foraging task.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This discrepancy may reflect methodological differences. In contrast to our experiments, the test subjects in the studies by Seferta et al (2001) and Webster & Lefebvre (2001) were never habituated to the foraging task apparatus to the extent that they fed from it within their normal, or 'control', latency to feed. Indeed, the research literature supports Greenberg's (2003) remark that animals shying away from unfamiliar situations, as reflected by, for example, their object neophobia, are unlikely to assess the costs and benefits of a novel foraging opportunity such as finding the solution to a novel foraging task.…”
Section: Discussionmentioning
confidence: 58%
“…In apparent contrast, object neophobia did correlate with flexibility in problemsolving attempts in five opportunistic avian species on Barbados (Webster & Lefebvre 2001). Furthermore, both feral pigeons, Columba livia, and Zenaida doves, Zenaida aurita, that were slow to feed from a novel apparatus were also slow at learning to open it (Seferta et al 2001). This discrepancy may reflect methodological differences.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Responses to novel objects are a well-established correlate of avian innovation, as measured by the time taken to solve novel foraging tasks. In feral pigeons Columba livia, zenaida doves Zenaida aurita, cut-throat nches Amadina fasciata, and zebra nches Taeniopygia guttata, those birds that are least reluctant to approach novel objects (a measure of inanimate object neophobia, henceforth 'object neophobia') are the quickest to solve novel tasks (Whittle, 1996;Seferta et al, 2001;Bouchard, 2002). Wild-caught Carib grackles Quiscalus lugubris are neophilic, in that they approach novel objects more rapidly than control objects (Reader and Lefebvre, unpubl.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Relationships between phenotypes and environments can be caused by various distinct mechanisms such as phenotypic plasticity, differential settlement, and/or the selective (dis)appearance of distinct types of individuals (Dingemanse et al, 2010). Several studies have demonstrated behavioral plasticity in response to urbanization (Lefebvre, 1995;Seferta et al, 2001;Bouchard et al, 2007;Levey et al, 2009). Song birds such as nightingales (Luscinia megarhynchos) and great tits (Parus major) have been shown to adjust song amplitude (Brumm, 2004) and frequency (Slabbekoorn and den Boer-Visser, 2006) to background noise.…”
Section: Introductionmentioning
confidence: 99%